Fetal Dose Evaluation for Pregnant Patients on Leksell Gamma Knife Perfexion/Icon - Hamáčková, Lucie; Novotný, Josef; Šimonová, Gabriela; Liščák, Roman; Chytka, Tomáš (Stereotactic and functional neurosurgery, 2024)
INTRODUCTION: It is a normal procedure to avoid the application of ionizing radiation during pregnancy. In very rare occasions, treatment can be performed, but doses to the fetus must be evaluated and reported, and the patient must sign informed consent. There can occur two types of damage caused by ionizing radiation - deterministic and stochastic effects. Deterministic effects may occur after reaching a certain threshold (100 mGy for this study); meanwhile, stochastic effects have no limit and their probability rises with dose. This study focuses on deterministic effects. CASE PRESENTATIONS: This study compares the dose measured on phantom for the area of the pelvis and the dose measured on 3 patients with dosimeters positioned on the pelvis irradiated on Leksell Gamma Knife Perfexion/Icon. The mean dose for measurement on phantom for the pelvis was 0.73 ± 0.76 mGy, and for the patients, it was 1.28 mGy, 0.493 mGy, and 0.549 mGy which is 80 times lower, 200 times lower, and 180 times lower than the threshold for deterministic effects, respectively. CONCLUSION: The measurement carried on phantom served as the base for drafting informed consent and provided initial proof that treatment can be safely delivered. Measurements performed on patients only confirmed that irradiation of pregnant patients on Leksell Gamma Knife Perfexion/Icon is safe relative to the deterministic effects. Nevertheless, pregnant patients should be treated with ionizing radiation only in very extraordinary situations.
Keywords: Pregnant; radiochirurgie; Female; Radiosurgery; Pregnancy; Humans; ženské pohlaví; Leksell Gamma Knife; Fetal dose; fantomy radiodiagnostické; lidé; Phantoms, Imaging; Icon; Perfexion; těhotenství